2011
DOI: 10.1007/s12223-011-0050-0
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic characterization of toxigenic group C and G streptococci isolated in Chennai, South India

Abstract: Background & objectives: Increasing resistance to erythromycin has been observed worldwide in group C and group G streptococci (GCS/GGS). The information available from India is scanty. The aim of the study was to identify erythromycin resistant GCS/GGS isolates in Chennai, south India, and to compare erythromycin resistant genotypes with emm types. Methods: One hundred and thirty one GCS/GGS isolates were tested for erythromycin resistance by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
5
6
0
Order By: Relevance
“…As reported previously, it has been verified that the M phenotype is linked to the mefA gene, which is involved in an active efflux pump system for 14-and 15-membered macrolides and lincosamines (Clancy et al, 1996), whilst the ermA gene is correlated with the iMLS B phenotype (Weisblum, 1995). A previous study (Prabu & Menon, 2013) reported rates of 9.2 and 3.1 % for the iMLS B and M phenotypes, respectively, which are similar to those found for our SDSE collection. Although ermB has been detected in other SDSE collections (Van Leer Buter et al, 2010;Prabu & Menon, 2013;Takahashi et al, 2011), the isolates from Brazil only harboured ermA, probably due to the high clonal structure of the collection.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As reported previously, it has been verified that the M phenotype is linked to the mefA gene, which is involved in an active efflux pump system for 14-and 15-membered macrolides and lincosamines (Clancy et al, 1996), whilst the ermA gene is correlated with the iMLS B phenotype (Weisblum, 1995). A previous study (Prabu & Menon, 2013) reported rates of 9.2 and 3.1 % for the iMLS B and M phenotypes, respectively, which are similar to those found for our SDSE collection. Although ermB has been detected in other SDSE collections (Van Leer Buter et al, 2010;Prabu & Menon, 2013;Takahashi et al, 2011), the isolates from Brazil only harboured ermA, probably due to the high clonal structure of the collection.…”
Section: Discussionsupporting
confidence: 90%
“…A previous study (Prabu & Menon, 2013) reported rates of 9.2 and 3.1 % for the iMLS B and M phenotypes, respectively, which are similar to those found for our SDSE collection. Although ermB has been detected in other SDSE collections (Van Leer Buter et al, 2010;Prabu & Menon, 2013;Takahashi et al, 2011), the isolates from Brazil only harboured ermA, probably due to the high clonal structure of the collection.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…[356] Coir pith, ah igh-lignin-content byproduct of coconut fibers, and thus, waste from the coir industry,c an be used as a carbon source by Azotobacter beijerinickii for P(3HB) biosynthesis. [357] Moreover, spent coffee grounds, aw idely available waste from coffee beverages, contain about 15 wt %o fv egetal oil, which can be simply extracted andc onverted into P(3HB) by C. necator. [358,359] Subsequently,h exose-rich spent coffee ground hydrolysates can be used by B. cepacia to produce P(3HB-co-3HV), with levulinic acid present in spent coffee grounds as the 3HV precursor.…”
Section: Carbohydratesmentioning
confidence: 99%